Pengaruh Sumber Air Tidak Layak terhadap Tingkat Risiko Stunting di Provinsi Gorontalo - Fery Rahmat Angriawan Bagu; , Fitryane Lihawa; Dewi Wahyuni K. Baderan (Lembaga Pengembangan Kinerja Dosen, 2024)
Stunting is a major health problem in Indonesia which affects physical, cognitive growth and future disease risk. This study aims to analyze the effect of drinking water source quality on the prevalence of stunting in Gorontalo Province. The research is a quantitative research. The source of data in this study is secondary data with a target number of 208,303 households who are couples of childbearing age, pregnant women, and families with children 0-59 months in Gorontalo Province. Analysis result showed that there is a significant influence between drinking inadequate water and the risk of stunting with a sig value. 0.003, and the value of R = 0.956 and R² = 0.913, which means that 91.3% of the drinking water variable affects the level of stunting risk. Inadequate water increases the risk of infections such as diarrhea, which inhibits the absorption of nutrients. Providing clean water should be a priority to reduce stunting. However, this intervention needs to be complemented by improved sanitation, community education, and improved child nutrition. This study is expected to be the basis of strategic policies to reduce the prevalence of stunting in Indonesia.